THE EFFECT OF CAREER DEVELOPMENT, EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE AT INSTITUT ABDUL HALIM HASAN BINJAI - Habibah Aulia Adni Nst; Desi Astuti (Universitas Muhammadiyah Bengkulu, 2026)
This research investigates how career development, employee engagement, and work discipline affect employee performance, with work motivation positioned as an intervening variable at Institut Syekh Abdul Halim Hasan Binjai, involving 41 employees as the sample. Using a quantitative method with Structural Equation Modeling (SEM) based on Partial Least Square (PLS), the study found that career development significantly and positively influenced performance, indicated by a T-statistic of 5.744 > 1.96 and a P-value of 0.000 < 0.05. Employee engagement also had a positive and significant effect (T-statistics = 3.549; P-value = 0.001). In contrast, work discipline did not show a significant impact (T-statistics = 0.839; P-value = 0.406). Work motivation had a significant yet negative effect on performance (T-statistics = 2.353; P-value = 0.023), which points to a mismatch between motivation and workload. Mediation results showed that career development had no significant indirect effect through motivation, while employee engagement demonstrated a meaningful mediating influence (T-statistics = 2.572; P-value = 0.014). Meanwhile, work discipline did not have an indirect effect. Overall, career development and employee engagement emerge as the key drivers of performance, with motivation acting only as a partial mediator